Improving ambiguity resolution and cycle slip detection from combined triple-frequency GNSS observations - Zhao, Dongsheng (2019)
This thesis improves ambiguity resolution and cycle slip detection taking advantage of the benefits of combined triple-frequency signals. Multi Global Navigation Satellite System (GNSS) are transmitting triple-frequency signals. Compared to dual-frequency, the additional signal is anticipated to bring more combinations with longer wavelength, better elimination of ionospheric delay and lower measurement noise.